A distal metatarsal osteotomy for hallux rigidus - (:unkn) unknown (My University, 2010)
Hallux rigidus is a mild to severe degenerative arthritis of the first metatarsophalangeal joint of the foot. The symptoms usually result from cartilage wear, altered joint mechanics, and osteophyte formation particularly on the dorsal aspect of the first metatasal head. Although cheilectomy is used with predictable success to treat grade 1 and grade 2 cases with Hallux rigidus, arthrodesis is the most commonly used tecnique to treat the advanced cases. In this report, we aimed to present a new tecnique of distal metatarsal ostetomy for surgical correction of advanced hallux rigidus with cheilectomy. © 2010 by Lippincott Williams & Wilkins.
Keywords: Cheilectomy; Distal; Hallux rigidus; Metatarsal; Osteotomy